2014
DOI: 10.1007/s11306-014-0706-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes associated metabolomic perturbations in NOD mice

Abstract: Non-obese diabetic (NOD) mice are a widely-used model oftype1 diabetes (T1D). However, not all animals develop overt diabetes. This study examined the circulating metabolomic profiles of NOD mice progressing or not progressing to T1D. Total beta-cell mass was quantified in the intact pancreas using transgenic NOD mice expressinggreen fluorescent protein under the control of mouse insulin I promoter.While both progressor and non-progressor animals displayed lymphocyte infiltration and endoplasmic reticulum stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 59 publications
6
37
0
Order By: Relevance
“…Increased representation of BCAA metabolism genes in the PAT metagenome as well as increased serum levels of leucine and isoleucine is consistent with higher BCAA serum levels in mice 43 and in humans who progress T1D 44 . The choline metabolites, TMAO and betaine, derived from gut microbiota, have associations with atherosclerosis 45 .…”
Section: Discussionmentioning
confidence: 52%
“…Increased representation of BCAA metabolism genes in the PAT metagenome as well as increased serum levels of leucine and isoleucine is consistent with higher BCAA serum levels in mice 43 and in humans who progress T1D 44 . The choline metabolites, TMAO and betaine, derived from gut microbiota, have associations with atherosclerosis 45 .…”
Section: Discussionmentioning
confidence: 52%
“…Importantly, we found that chronic hyperglycemia (Ն250 mg/dl) and overt T1D manifested only in mice that lost ϳ70% of their total ␤-cell mass (23). Using an untargeted metabolomics approach, we performed an initial evaluation of primary metabolites in plasma of young (Ͻ25 wk) and old (Ն25 wk) nonprogressors (nondiabetic) vs. progressors (diabetic) to reveal distinct metabolomic pathways involved in disease progression (23). In the present study, we largely extended these investigations to capture alterations in primary metabolism, complex lipids, and lipid signaling mediators in the plasma of nonprogressors and progressors with the overall aim(s) of identifying circulating factors linked to disease progression and, potentially, ␤-cell destruction and dysfunction.…”
mentioning
confidence: 76%
“…T1D and performed an initial screening of primary metabolites in the plasma of these mice with the aims of identifying circulating factors linked with ␤-cell viability and/or T1D progression (23). In the current study, we aimed to expand upon our initial observations by using a multiplatform approach to recapitulate our initial metabolomic findings in addition to capturing perturbations in the lipidome and lipid signaling mediators.…”
Section: Legend)mentioning
confidence: 99%
See 1 more Smart Citation
“…The top 10% feature model was evaluated using Monte Carlo training and testing cross-validation and permutation testing (18). Internal training and testing was done by further splitting the training set into 2/3 pseudo-training and 1/3 pseudo-test sets, while preserving individual patients’ tumor and control tissue pairs.…”
Section: Methodsmentioning
confidence: 99%